Անաստաս վարդապետի կազմած Երուսաղեմի հայկական վանքերի ցուցակի ժամանակի հարցի շուրջ - Պավել Չոբանյան (ՀՀ ԳԱԱ հրատ.)
Список армянских монастырей Иерусалима, составленный архимандритом Анастасием и введенный в научный оборот Г. Алишаном в конце XIX в.,— важный средневековый памятник армянской письменности. The List of the Armenian monasteries in Jerusalem was compiled by Archimandrite Anastasius and brought in the field of scientific research at the end of the 19th century by Gh.Alishan. It is an important mediaeval monument of the Armenian writings.
Keywords: History; B Philosophy; Psychology; Religion; Philology; Linguistics; Language and Literature; BR Christianity; D History